The Impacts of Climate Change and Porous Pavements on Combined Sewer Overflows: A Case Study of the City of Buffalo, New York, USA - Roseboro, Andrew; Torres, Maria Nariné; Zhu, Zhenduo; Rabideau, Alan J. (Frontiers in Water, 2021)
Combined sewer overflows (CSOs) release pollutants collected in urban runoff into local waterways, impacting both aquatic life and human health. The impact of climate change on precipitation may result in an increase in the frequency and magnitude of heavy precipitation events, with a corresponding increase in CSO discharges. The installation of Green Infrastructure (GI) such as Porous Pavements (PP) is a resilient approach to mitigate CSO events. However, an understanding of the impact of climate change on CSO events and the effectiveness of GI practices is crucial for designing sustainable urban stormwater management systems. Using the Storm Water Management Model (SWMM), the performance of PP as a CSO abatement strategy was studied for the city of Buffalo, New York, USA. This paper used the Intensity-Duration-Frequency (IDF) curves for current (1970-1999) and future (2070-2099) design rainfall scenarios, with four rainfall durations (1 hour, 6 hours, 12 hours, and 24 hours) and four return periods (2 years, 10 years, 50 years, and 100 years). The simulation results show that 1) current 100-year events generate CSO volumes similar to predicted 50-year events; 2) CSO volumes could increase by 11-73% in 2070-2099 compared to 1970-1999 when no GI intervention is performed, and 3) the installation of PP can reduce 2-31% of future CSO volume. This case study demonstrates the regional CSO challenges posed by climate change and supports the use of GI as a mitigation strategy.